2019
DOI: 10.1111/nan.12552
|View full text |Cite
|
Sign up to set email alerts
|

A cortical microvascular structure in vascular dementia, Alzheimer's disease, frontotemporal lobar degeneration and nondemented controls: a sign of angiogenesis due to brain ischaemia?

Abstract: AimsWe observed a microvascular structure in the cerebral cortex that has not, to our knowledge, been previously described. We have termed the structure a ‘raspberry’, referring to its appearance under a bright‐field microscope. We hypothesized that raspberries form through angiogenesis due to some form of brain ischaemia or hypoperfusion. The aims of this study were to quantify raspberry frequency within the cerebral cortex according to diagnosis (vascular dementia, Alzheimer's disease, frontotemporal lobar d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 73 publications
(104 reference statements)
2
27
0
Order By: Relevance
“…The number of capillaries in the frontal cortex, as revealed with GLUC-t immunohistochemistry, is significantly increased in all GGT cases when compared with controls in the present series. Our hypothesis is that this effect is due to the neuronal loss and cortical atrophy of frontal degeneration in GGT cases, together with angiogenesis (capillary sprouting) induced by protein pathology and neuroinflammation, as proposed in ageing and other brain diseases [93].…”
Section: Astrocytopathy and Oligodendrocytopathy In Ggtmentioning
confidence: 90%
“…The number of capillaries in the frontal cortex, as revealed with GLUC-t immunohistochemistry, is significantly increased in all GGT cases when compared with controls in the present series. Our hypothesis is that this effect is due to the neuronal loss and cortical atrophy of frontal degeneration in GGT cases, together with angiogenesis (capillary sprouting) induced by protein pathology and neuroinflammation, as proposed in ageing and other brain diseases [93].…”
Section: Astrocytopathy and Oligodendrocytopathy In Ggtmentioning
confidence: 90%
“…Our pathway enrichment and deconvolution analyses pointed toward increased blood vessel abundance and growth in FTD brains compared to controls, which is consistent with the results from the RiMod-FTD proteomics data (Mediema et al, manuscript in preparation). It is generally not known how and if the vasculature system is involved in FTD pathogenesis, although recent studies have observed abnormalities in a mouse model of tau pathology and post-mortem human brains 22,23 . To our knowledge, angiogenesis as a pathological feature in several genetic FTD subtypes has not been reported before and therefore depicts an important subject to study for future FTD research.…”
Section: Discussionmentioning
confidence: 99%
“…3A). Another recent study observed a particular microvascular structure with increased frequency in brains of patients with frontotemporal lobar degeneration (FTLD) 23 and Park et al have shown that soluble tau can interfere with nitric oxide production and thus lead to reduced vasodilation of blood vessels, ultimately leading to insufficient blood supply 24 . To better understand transcriptional changes and regulatory mechanisms, it is often helpful to cluster genes into modules with similar expression or function.…”
Section: Vulnerability Of Excitatory Neurons and Enrichment Of Endothmentioning
confidence: 99%
“…3a). Another recent study observed a particular microvascular structure with increased frequency in brains of patients with frontotemporal lobar degeneration (FTLD)23 and Park et al have shown that soluble tau can interfere with nitric oxide production and thus lead to reduced vasodilation of blood vessels, ultimately leading to insufficient blood supply24 .…”
mentioning
confidence: 99%
“…In a recent review, Molnár and colleagues have discussed several available drugs that could potentially regulate necroptosis39 , highlighting the potential of this pathway as a drug target for developing therapies for FTD.Our pathway enrichment and deconvolution analyses pointed toward increased blood vessel abundance and growth in FTD brains compared to controls, which is consistent with the results from the RiMod-FTD proteomics data (Mediema et al, manuscript in preparation). It is generally not known how and if the vasculature system is involved in FTD pathogenesis, although recent studies have observed abnormalities in a mouse model of tau pathology and post-mortem human brains22,23 . To our knowledge, angiogenesis as a pathological feature in several genetic FTD subtypes has not been reported before and therefore depicts an important subject for FTD research.…”
mentioning
confidence: 99%